Connectors with assessed quality, for use in d.c., low-frequency analogue and in digital high speed data applications. Printed board connectors. Detail specification for two-part connectors with shielding and a basic grid of 2, 5 mm Part 4-103, (15th June 1999) - British Standards Institution,
No abstract available